The Roles of Export of Coffee Commodity and Macroeconomics Factors on Unemployment in Indonesia - Hendrasto, Nur; Ibrahim, Muhammad Yusuf; Novianti, Tanti (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2023)
Coffee as the second largest agricultural commodity export has contributed to the economies of various countries, including Indonesia. In addition to looking at the role of coffee commodity exports, an analysis of macroeconomic factors' impact on Indonesia's unemployment rate is also analyzed. Because it is known that the unemployment rate is not only caused by one sector but some things influence it, including macroeconomic factors. This study analyzes the role of coffee commodity exports and macroeconomic factors, including GDP, inflation, and interest rates, on Indonesia's unemployment rate. The data used in this study is interpolated secondary data for the period 2000 to 2021. The estimation method used in this study is Robust Least Square (ROBUSTLS) which will then be estimated again using the Autoregressive Distributed Lag (ARDL) method as a robustness test. The estimation results using the ROBUSTLS method prove that coffee commodity exports and macroeconomic factors significantly affect Indonesia's unemployment rate in aggregate. This form of influence is negative for coffee commodity exports (ExpCof), gross domestic product (GDP), and interest rate (IR). While inflation (Inf) has a positive impact on the unemployment rate (Ump). These findings are reinforced by the estimation results using the ARDL method with the result that ExpCof, GDP, and Inf have a significant relationship to Ump, while Inf is not as significant as the findings from the estimation results using the ROBUSTLS method.